Students Moral Education as 'Moral Force' in Social Life - Syelia Febriani; Firga Nevi; Suneti; Shelawati Emilia; Anita Khoerunisa; Ina Patika Sari; Masduki Asbari (AGUSPATI RESEARCH INSTITUTA, 2022)
The purpose of this paper is to create a young generation, especially students who have good morals, as their role as a 'moral force' in social life. The method of delivering material in this activity is a zoom meeting through lectures and discussions. The definition of a learning contract in this case is an agreement between lecturers and students about various things in lecture activities that will be carried out in one semester. This learning contract includes outward rules, rules of conduct, and rules of order that contain obligations, prohibitions, and sanctions for violations committed by students. Through the implementation of learning contracts in this lecture, students can also increase the moral foundation in their role as a 'moral force' in social life. Where the purpose of these activities is that students must provide the best moral example according to their intellectual level so that the people who follow are also able to become moral people.